Revalidation of the Brazilian Atlantic Forest dung beetle species Coprophanaeus (Metallophanaeus) machadoi (Pereira & d’Andretta, 1955) (Coleoptera: Scarabaeidae: Scarabaeinae: Phanaeini) based on morphological and distributional evidence - Cupello, Mario; Vaz-De-Mello, Fernando Z. (Zootaxa, 2014)
Coprophanaeus machadoi, species described based on a single male from Minas Gerais, was recently synonymized with C. saphirinus (Sturm, 1826). In this work, based on examination of more than 500 specimens from Brazilian Atlantic Forest, we introduce new evidence supporting the validity of C. machadoi, including differences in male pronotal ornamentation, in the form of the parameres, and in distribution. We also describe for the first time the female of C. machadoi and discuss the intraspecific color variation of C. saphirinus.